Fibre length by electronic image analysis - Hoelstad, Torsten (Danmarks Geologiske Undersøgelse Serie C, 1992)
A number of electronic image analysis techniques have been applied to preparations of glass fibres obtained from polymer based composites (PES and PPS matrix) in order to automate length measurements. The image analysis sequence developed is described in detail. The functions of the sequence are based mainly on aspects of filtering in the spatial domain by means of convolution, mathematical morphology and conditional measuring. The key image analysis function is directional erosion. Using glycerol jelly strew preparations and transmitted light, the length of 500 glass fibres can be automatically measured in approximately 15 minutes with an array processor-based image analysis system (IBAS 2). The image analysis method is tolerant of impurities and variations in fibre preparation density; the method produces consistent results and errors due to misinterpretation are negligible.